Pengaruh Kualitas Produk, Harga Dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Rental Alat Camping : Survei Pada Pelanggan Astrajingga Adventure - Hani Nurhayani; Budhi Wahyu Fitriadi; Depy Muhamad Pauzy (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This study aims to determine the effect of product quality, price and service quality on customer loyalty camping equipment rental. the method used is a case study, data obtained through questionnaires to Astrajingga Adventure customers. Withdrawal of samples using purposive sampling technique and the method of analysis used is multiple linear regression analysis method. The results of the research show that product quality, price, service quality and customer loyalty are included in the good classification. Simultaneously product quality, price and service quality have a significant effect on customer loyalty for Astrajingga Adventure camping equipment rental. Partially the product quality variable has no significant effect on camping equipment rental customer loyalty, the price perception variable has a significant effect on camping equipment rental customer loyalty, similarly the service quality variable has a significant effect on camping equipment rental customer loyalty Astrajingga Adventure.